Listed companies in Malaysia and Singapore by market capitalization - a comparative risk, risk diversification benefits and performance analysis - Sea, Hui Ying (2019)
This study investigates the performance index, risk features and risk diversification benefits of Malaysia Listed Companies and Singapore Listed Companies from January 2009 - December 2018. The performance measures employed in this study are Sharpe Ratio, Treynor Ratio and Jensen Alpha. However, the risk evaluation methods are Beta, R-Square, Total Risk, Systematic Risk and Unsystematic Risk. The Diversifiability Measure has also been employed to measure the risk diversification benefits of the investments. The total risk of Singapore listed companies is higher than Malaysia listed companies, while the Beta values for both countries are less than one. This implies that listed companies in both countries are less risky when compared against their respective national market indexes. The lower R-squared values in Malaysia Listed Companies as compared to Singapore suggest that Malaysia Listed Companies has a more opportunities for diversification according to the formulas by Diversifiability Measures. The results conclude that the listed companies in Malaysia performed better than the listed companies in Singapore in terms of its Sharpe Ratio and Treynor ratio. In terms of Jensen Alpha, although both of the countries listed companies yielded a negative value, but the Malaysia Listed Companies still marginally performed better than the Singapore Listed Companies. The total risk of Singapore listed companies is higher than Malaysia listed companies, while the Beta values for both countries are less than one. This implies that listed companies in both countries are less risky when compared against their respective national market indexes. The lower R-squared values in Malaysia Listed Companies as compared to Singapore suggest that Malaysia Listed Companies has a more opportunities for diversification according to the formulas by Diversifiability Measures. The best/worst performers in both countries is also determined in this study. The findings provide good insights to investors who are considering the addition of the countries' shares into their portfolio investments.